Crash energy absorption aspects of reinforced concrete barriers with natural rubber sheet - Lwin Lwin Aung; Amphon Jarasjarungkiat (AIP conference proceedings, 2021)
These days, vehicles are widely developed because of the latest technology. As a result, roadside barriers are used not only to minimize the speed of vehicles but also to prevent crossing into the opposite lanes. Many technologies are used to improve the strength of barriers. On the other hand, the production of natural rubber in Thailand is higher than in other Asian countries. The ministry of transportation is focusing on using rubber in roadside barriers. Therefore, in this study, three different types of vehicles with 920, 1575, and 2013 kg at a constant velocity of 35 mph for frontal impact were used to compare the strength of reinforced concrete barriers with and without natural rubber by using non-linear dynamic finite element analysis. Results proved that the barriers with rubber sheets stored energy absorption better than those without rubber sheets.
Keywords: Transportation Safety and Impact Analysis; Structural Response to Dynamic Loads; Natural Fiber Reinforced Composites